2008
DOI: 10.1093/ndt/gfm897
|View full text |Cite
|
Sign up to set email alerts
|

A differential diagnostic model of diabetic nephropathy and non-diabetic renal diseases

Abstract: Background. Renal diseases in diabetes include diabetic nephropathies (DN) and non-diabetic renal diseases (NDRD). The clinical differentiation between these two categories is usually not so clear and effective. This study aims to develop a quantified differential diagnostic model. Methods. We consecutively screened the diabetic patients with overt proteinuria but no severe renal failure for kidney biopsy from 1993 to 2003. The finally enrolled 110 patients were divided into two groups according to pathologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

34
108
10
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(160 citation statements)
references
References 15 publications
34
108
10
8
Order By: Relevance
“…These findings are in contrast to reports from Southeast Asia which IgA nephropathy (up to 65%) was the most common NDRD. 5,6 Studies have shown that in the US FGS 14 and in India AIN 7 were the prevail pathology. These contrasting reports in various regions are due to both distinctive common glomerular diseases and perhaps different criteria (and threshold) for kidney biopsy in type 2 diabetes patients with atypical renal presentations.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These findings are in contrast to reports from Southeast Asia which IgA nephropathy (up to 65%) was the most common NDRD. 5,6 Studies have shown that in the US FGS 14 and in India AIN 7 were the prevail pathology. These contrasting reports in various regions are due to both distinctive common glomerular diseases and perhaps different criteria (and threshold) for kidney biopsy in type 2 diabetes patients with atypical renal presentations.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12] The most common pathologies in NDRD group were MN (45%) and FGS (30%), respectively. In the DN + NDRD group, although AIN (60%) was the most common lesion, IgA nephropathy (20%) was the prevalent glomerulopathy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations